Is ball-possession style more physically demanding than counter-attacking? The influence of playing style on match performance in professional soccer - Forcher, Leon; Forcher, Leander; Wäsche, Hagen; Jekauc, Darko; Woll, Alexander; Gross, Timo; Altmann, Stefan (Frontiers in Psychology, 2023)
In Soccer, the offensive style of play describes characteristic behavioral features of the players at team level during the offensive phase of matches. This study aimed to investigate the effect of offensive playing style (i.e. while in ball possession) on physical and technical match performance during offensive play as well as success-related factors.The sample consisted of official tracking and event data of 153 matches of the 2020/21 German Bundesliga season. For every team in every match an offensive playing style coefficient was calculated to locate teams on a continuum between ball possession and counter-attacking style. This calculation contains eleven technical and physical performance parameters and has already been validated. In addition, dependent physical (e.g. sprinting distance), technical (e.g. passes), and success-related (e.g. goals) variables were examined. A separate linear mixed model was calculated for each dependent variable.While teams with lower playing style coefficient values (= counter-attacking style) covered more highintensity (p≤0.01; R 2 =0.13) and sprinting distances per second in possession (p≤0.01; R 2 =0.14), teams with higher playing style coefficient values (= ball possession style) were physically more demanded over a whole match (e.g. more accelerations (p≤0.01; R 2 =0.69), decelerations (p≤0.01; R 2 =0.69), highintensity (p≤0.01; R 2 =0.36), sprint distance (p=0.03; R 2 =0.08)). Furthermore, teams with higher playing style coefficient values played more horizontal passes (p≤0.01; R 2 =0.73) and revealed better passing success rates (p≤0.01; R 2 =0.17). ...